TENDENCIES AND PROSPECTS OF THE CLOSED UNIT INVESTMENT FUNDS MARKET - Antonina V. Spiridonova (Статистика и экономика, 2016)
The essence of closed unit investment funds is stated in the article. Their differences from the open and interval funds are examined. It is marked out the tendencies of development of the market of closed unit investment funds. The peculiarities of taxation and functions of the closed funds are considered. The prospects of development of the closed unit investment funds are given.